Kajian Penggunaan Platform Robot Otto DIY Sebagai Pendukung Model Pembelajaran Berbasis STEM - Tatik Juwariyah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2022)
The appropriate learning methods and learning models in the future have always been an interesting topic of study. The topic of robotics is one of the topics that represent STEM-based learning (Science Technology Engineering and Mathematics) developed in the future. This paper describes how STEM is introduced and applied in schools. The method used is to conduct surveys and socialization of STEM-based learning by introducing the ottodiy.com platform as one of the STEM platforms that already has many communities in various countries. The participants of the socialization were introduced to the menus provided by the platform. The focus is the topic of robotics and the menus introduced are menus related to robotics such as build your own robot, design your own robot, engineer your own robot, code your own robot, and coding with Arduino. From the socialization activities, a survey was conducted to collect response data or testimonials from platform users. From the survey results using Google Form media, 90.5% of users are familiar with STEM learning, 85.7% agree that STEM is introduced starting from the basic education level, 52.4% have looked for STEM platform references, 100% of participants have never been familiar with the Ottodiy.com platform, 90.5% were interested in learning with it, and 85.7% stated that they had difficulties to understand the menus presented by the platform due to the participants' limited English skills. However, overall participants, 80%-95% were interested in getting follow-up training related to STEM-based learning.